Non est crimen amor. Lateinische Liebesdichtung im Umkreis des Petrus Abaelardus - Wollin, Carsten (Sacris erudiri, 2013)
The five medieval Latin love poems presented in this article come from two small collections of songs that may have originated in the years about 1100-1140 in the entourage of the famous philosopher and theologian Peter Abelard (1079-1142/43) and his pupil Hilary of Orléans : the so-called Carmina Florentina and a group of the Carmina Burana (CB 88a, 95, 116-121). Both collections exhibit striking similarities : their authors exclusively make use of the techniques of the lyric-self (Persona-Dichtung) as distinct from the empirical author, and describe, even praise their characters’ sentiments on human love without any moral censure. In this respect the songs bear witness of the beginning emancipation of human love from the ascetic and repressive teaching of the medieval church in the twelfth century.